Psychological work with inmates, depending on the offense - Roman Makoviychuk (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
Article partially reveals the process of implementation of the pilot study within the program of psycho diagnostic efficiency of resocialization. These data indicate the selection of the most common psychological differences among groups convicted of similar offenses in content. And on the basis of the study the peculiarities of psychological work with inmates, depending on the type of offense.